Lingkungan Kerja, Karakteristik Individu, Motivasi dan Kepuasan Kerja Pilot Maskapai Lion Air - Luh Dewi Trimurdani Mas Ningrat (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe purpose of this study is to influence the work environment and individual characteristics of the pilot's motivation and the influence of the work environment on individual characteristics and motivation on the pilot's job satisfaction at Lion Air Airlines. The design of this research is quantitative, is the relationship of causality between variables. The study was conducted on Lion Air Airlines. Data collection techniques used questionnaires to 177 Lion Air Airlines pilots. Data were analyzed by data analysis technique Structure Equation Modeling with AMOS program. The results showed that the direct effects of work environment variables on motivation were significant. This means that the better the working environment, the higher the pilot's work motivation. The direct effects of individual variable variables on motivation are significant. This means that the better the individual characteristics of the pilot, the higher the pilot's work motivation. The direct effects of work environment variables on pilot job satisfaction are significant. This means that the better the working environment the higher the job satisfaction of the pilot. The direct effects of individual variable variables on pilot job satisfaction are significant. This means that the better the individual characteristics of the pilot, the higher the pilot's job satisfaction. The direct effects of motivational variables on pilot job satisfaction are significant. This means that the higher the work motivation of the pilot, the higher the pilot's job satisfaction.